Personal values and political activism: A cross‐national study. (7th March 2014) - Vecchione, Michele; Schwartz, Shalom H.; Caprara, Gian Vittorio; Schoen, Harald; Cieciuch, Jan; Silvester, Jo; Bain, Paul; Bianchi, Gabriel; Kirmanoglu, Hasan; Baslevent, Cem; Mamali, Catalin; Manzi, Jorge; et al.
<x xml:space="preserve">Abstract</x> Using data from 28 countries in four continents, the present research addresses the question of how basic values may account for political activism. Study 1 (N = 35, 116) analyses data from representative samples in 20 countries that responded to the 21‐item version of the Portrait Values Questionnaire (PVQ‐21) in the European Social Survey. Study 2 (N = 7, 773) analyses data from adult samples in six of the same countries (Finland, Germany, Greece, Israel, Poland, and United Kingdom) and eight other countries (Australia, Brazil, Chile, Italy, Slovakia, Turkey, Ukraine, and United States) that completed the full 40‐item PVQ. Across both studies, political activism relates positively to self‐transcendence and openness to change values, especially to universalism and autonomy of thought, a subtype of self‐direction. Political activism relates negatively to conservation values, especially to conformity and personal security. National differences in the strength of the associations between individual values and political activism are linked to level of democratization.